Interventions of Reclamation Technologies for Sand/silt deposited Matmora area of Lakhimpur District, Assam - Bordoloi, Arundhati; Bora, Buddha; Bhattacharya, Sameeron; Deka, Niranjan; Goswami, Jogesh (International Journal of Bio-resource and Stress Management, 2019)
An On-farm Trial was carried out in the Matmora area of Lakhimpur District, Assam, India where sand/silt deposition is causing threats to the farming community by covering the cultivable areas with huge deposition of river sand. The mighty Brahmaputra carried sand/silt along with its fresh flood and covered the green fertile land of Matmora. Participatory Rural appraisal (PRA) was done to evaluate farmers’ knowledge on the severity of problem as well as farmers response to the scientific land reclamation technologies. Only 5% of the surveyed farmers knew about the soil reclamation technologies and only 1% farmers adopted such technologies to reclaim the sand/silt deposited fields of Matmora. In order to improve the soil fertility status of the sand/silt deposited area, scientific interventions were done as On-farm Trial (OFT) with the introduction of leguminous crops like blackgram, frenchbean and a highly remunerative crop like garlic with application of huge amount of organic matter. After adopting the interventions technology for sand/silt deposited area, significantly higher average productivity of 10.75 q ha-1 of Blackgram was obtained with fertilizer application @ 50% NPK+2 t of FYM ha-1. 150.04 qha-1 French bean was obtained with fertilizer application @ 50% NPK+40t FYM ha-1 and 18.48 q ha-1 garlic was recorded with fertilizer application @50%NPK+40 t FYM ha-1 as compared to the farmers practice. Treatments comprising leguminous crop with double dose of FYM resulted higher organic C content of soil, increased available N, P and K and reduction of soil pH in sand/silt deposited area of Matmora of Assam.